Fecal microbiota transplantation in patients with spinal cord injury with recurrent Clostridioides difficile infection: a case report - Samford Wong, PhD, RD; Alastair Forbes, MD; Noureddine Kenssous, MSc; Anitha Naidoo, MD (The Journal of the International Society of Physical and Rehabilitation Medicine)
Objective:. Fecal microbiota transplantation (FMT) is an emerging treatment for Clostridioides difficile infection (CDI) through reconstruction of the gut microbiota, but its impact in people with spinal cord injury (PWSCI) is limited. The aim of this paper is to report the use of FMT in a PWSCI with CDI. Methods:. The FMT was conducted on October 30, 2019. Results:. A 72-year-old man with T8 complete paraplegia from compression of the spinal cord due to an epidural hematoma was referred. He has known severe pancreatic enzyme insufficiency, malabsorption, and a history of recurrent CDI. Despite intensive dietetic treatment (probiotics, enteral nutrition, and parenteral nutrition), and multiple courses of antibiotics (vancomycin and fidaxomicin at various doses and durations) for CDI, he continued to be CDI-positive. His CDI was successfully treated after 2 colonoscopically delivered FMTs. At the 24-month follow-up, he remains CDI-negative and reports improved independence. Although there has been considerable variability in the criteria for the FMT and its mode of delivery, FMT can be an option to treat recurrent CDI. Conclusion:. This case report reports a PWSCI with recurrent CDI who has been successfully treated with FMT and remains in long-term remission. It supports the consideration of FMT in PWSCI with CDI when antibiotic treatment has been unsuccessful.